Cofiring Effect of Using Sawdust on Exhaust Emissions at the Steam Power Plant - Muhammad Farras Ilham; Nazaruddin Sinaga (Universitas Muhammadiyah Sidoarjo, 2022)
Achieving the national energy mix in 2025 requires accelerating capacity development in new and renewable energy.Utilization of new and renewable energy potential aims to achieve the national energy mix target. One of the new renewable energy that has the potential to be developed in Indonesia is Biomass for fuel. One of the efforts to increase the use of biomass is by Cofiring. Biomass can be an effective alternative energy, in order to minimize the use of fossil fuels. The biomass is mixed into the coal bunker. The fuel mixture is flowed into the combustion chamber or furnace. Some of the advantages of doing biomass in PLTU include relatively lower investment and better environmental impact when compared to 100% coal. Cofiring PLTU has an effect on exhaust emissions, in evaluating the impact of exhaust emissions as a benchmark for environmental parameters, cofiring testing is carried out with reference to the Emission Quality Standard (BME).As a result, the effect of cofiring using 5% sawdust still has no significant effect on exhaust emissions at the CEMS (Continuous Emissions Monitoring System) PLTU. It is very possible that the type of coal used is still very influential on emission conditions, considering that the percentage of biomass used is still very small.